(untitled) (Actual Problems of Psychology in Educational Institutions, 2022)
The article is devoted to the comprehension of the psychological content of the most popular horror films for 2016-2017 years. Using the content-analysis of the video sequence of ten cinematography`s works for certain categories, there were established some unconscious factors, which determine what do the modern man afraid of the most.